A Phase II, Two-Stage Study of Letrozole and Abemaciclib in Estrogen Receptor–Positive Recurrent Endometrial Cancer. Issue 3 (29th September 2022) - Konstantinopoulos, Panagiotis A.; Lee, Elizabeth K.; Xiong, Niya; Krasner, Carolyn; Campos, Susana; Kolin, David L.; Liu, Joyce F.; Horowitz, Neil; Wright, Alexi A.; Bouberhan, Sara; Penson, Richard T.; Yeku, Oladapo; et al.
Abstract : PURPOSE: Estrogen receptor (ER)–positive endometrial cancers (ECs) are characterized by phosphatidylinositol 3-kinase (PI3K) and receptor tyrosine kinase (RTK)/RAS/β-catenin (CTNNB1) pathway alterations in approximately 90% and 80% of cases, respectively. Extensive cross-talk between ER, PI3K, and RTK/RAS/CTNNB1 pathways leads to both ligand-dependent and ligand-independent ER transcriptional activity as well as upregulation of cyclin D1 which, in complex with cyclin-dependent kinases 4 and 6 (CDK4 and CDK6), is a critical regulator of cell cycle progression and a key mediator of resistance to hormonal therapy. We hypothesized that the combination of the aromatase inhibitor letrozole and CDK4/6 inhibitor abemaciclib would demonstrate promising activity in this setting. METHODS: We conducted a phase II, two-stage study of letrozole/abemaciclib in recurrent ER-positive EC. Eligibility criteria included measurable disease, no limit on prior therapies, and all EC histologies; prior hormonal therapy was allowed. Primary end points were objective response rate by RECIST 1.1 and progression-free survival (PFS) rate at 6 months. RESULTS: At the data cutoff date (December 03, 2021), 30 patients (28 with endometrioid EC) initiated protocol therapy; 15 (50%) patients had prior hormonal therapy. There were nine total responses (eight confirmed), for an objective response rate of 30% (95% CI, 14.7 to 49.4), all in endometrioid adenocarcinomas. Median PFS was 9.1 months, PFS at 6 months was 55.6% (95% CI, 35.1 to 72), and median duration of response was 7.4 months. Most common ≥ grade 3 treatment-related adverse events were neutropenia (20%) and anemia (17%). Responses were observed regardless of grade, prior hormonal therapy, mismatch repair, and progesterone receptor status. Exploratory tumor profiling revealed several mechanistically relevant candidate predictors of response ( CTNNB1, KRAS, and CDKN2A mutations) or absence of response ( TP53 mutations), which require independent validation. CONCLUSION: Letrozole/abemaciclib demonstrated encouraging and durable evidence of activity in recurrent ER positive endometrioid EC.